Micro‐bubble transcranial Doppler ultrasound for exclusion of right‐to‐left circulatory shunts: Why should we provide the service?. Issue 4 (3rd March 2014) - Chiu, Albert H.; Haluszkiewicz, Elvie; McAuliffe, William
Summary Micro‐bubble transcranial Doppler ultrasound is a study used for the identification and quantification of a right‐to‐left circulatory shunt which can be implicated in stroke. It is an underused technique in many centres. Micro‐bubble transcranial Doppler ultrasound is non‐invasive, innocuous, quick and requires no fasting or sedation. Published literature also suggests almost perfect concordance with transoesophageal echocardiography and potentially greater sensitivity. We believe there is a great potential for neuroradiologists to provide this service as part of the diagnostic workup in patients with cryptogenic stroke.